Does place of death vary by deprivation for patients known to specialist palliative care services?. Issue 4 (1st December 2016) - Macfarlane, Michael; Carduff, Emma
Abstract : Objectives: Referral to, and usage of, specialist palliative care (SPC) services are not equitable and social deprivation may be a contributory factor in this. Deprivation may also affect the place of death of patients with cancer. No study, however, has investigated whether inequalities persist following referral to SPC services. This study investigates whether place of death varies by deprivation for patients known to SPC services. Methods: Place of death and postcode were obtained for 485 consecutive patients known to SPC services within NHS Lothian who died in 2014–2015. From this information, deprivation quintile (DQ) was derived using the Scottish Index of Multiple Deprivation (SIMD) database and place of death compared between DQs and analysed statistically. Results: Across all DQs, patients known to SPC services were more likely to die in the hospice than at home or in hospital. There was, however, a small but statistically significant difference in the ratio of hospital deaths compared to hospice deaths between the DQs, with higher death rates in hospital for the most deprived compared to the least deprived and higher death rates in the hospice for the least deprived compared to the most deprived. Conclusions: This study suggests that even after referral to specialist palliative care services variation in place of death by deprivation persists. Greater deprivation is associated with increased likelihood of dying in hospital and decreased likelihood of dying in a hospice, although no difference was noted for home deaths.